The magnitude of global marine species diversity - Wilson, Simon (My University, 2012)
Background The question of how many marine species exist is important because it provides a metric for how much we do and do not know about life in the oceans. We have compiled the first register of the marine species of the world and used this baseline to estimate how many more species, partitioned among all major eukaryotic groups, may be discovered. Results There are ~226,000 eukaryotic marine species described. More species were described in the past decade (~20,000) than in any previous one. The number of authors describing new species has been increasing at a faster rate than the number of new species described in the past six decades. We report that there are ~170,000 synonyms, that 58,000?72,000 species are collected but not yet described, and that 482,000?741,000 more species have yet to be sampled. Molecular methods may add tens of thousands of cryptic species. Thus, there may be 0.7?1.0 million marine species. Past rates of description of new species indicate there may be 0.5 ? 0.2 million marine species. On average 37% (median 31%) of species in over 100 recent field studies around the world might be new to science. Conclusions Currently, between one-third and two-thirds of marine species may be undescribed, and previous estimates of there being well over one million marine species appear highly unlikely. More species than ever before are being described annually by an increasing number of authors. If the current trend continues, most species will be discovered this century.
PUBLISHED
Keywords: Marine species; Neuroscience; Smart & Sustainable Planet